Connectivity calculus of fractal polyhedrons. Issue 4 (April 2015) - Molina-Abril, Helena; Real, Pedro; Nakamura, Akira; Klette, Reinhard
Abstract: The paper analyzes the connectivity information (more precisely, numbers of tunnels and their homological (co)cycle classification) of fractal polyhedra. Homology chain contractions and its combinatorial counterparts, called homological spanning forest (HSF), are presented here as an useful topological tool, which codifies such information and provides an hierarchical directed graph-based representation of the initial polyhedra. The Menger sponge and the Sierpiński pyramid are presented as examples of these computational algebraic topological techniques and results focussing on the number of tunnels for any level of recursion are given. Experiments, performed on synthetic and real image data, demonstrate the applicability of the obtained results. The techniques introduced here are tailored to self-similar discrete sets and exploit homology notions from a representational point of view. Nevertheless, the underlying concepts apply to general cell complexes and digital images and are suitable for progressing in the computation of advanced algebraic topological information of 3-dimensional objects. Abstract : Highlights: This paper analyzes the connectivity information of fractal polyhedra. This paper recalls homology strong-deformation retracts as an appropriate tool for doing so. This paper illustrates the relevance of this tool for Menger sponge and Sierpinski pyramids. This paper provides examples and detailed proofs.